The neuroprotective effect of pretreatment with carbon dots from Crinis Carbonisatus (carbonized human hair) against cerebral ischemia reperfusion injury - Zhang, Yue; Wang, Suna; Lu, Fang; Zhang, Meiling; Kong, Hui; Cheng, Jinjun; Luo, Juan; Zhao, Yan; Qu, Huihua (Journal of nanobiotechnology, 2021)
Background Cerebral infarction and cerebral hemorrhage, also known as “stroke”, is one of the leading cause of death. At present, there is no real specific medicine for stroke. Crinis Carbonisatus (named Xue-yu-tan in Chinese), produced from carbonized hair of healthy human, and has been widely applied to relieve pain and treat epilepsy, stroke and other diseases in China for thousands of years. Results In this work, a new species of carbon dots derived from Crinis Carbonisatus (CrCi-CDs) were separated and identified. And the neuroprotective effect of carbon dots from CrCi were evaluated using the middle cerebral artery occlusion (MCAO) model. Neurological deficit score and infarction volume was assessed, evans blue content of ischemic hemispheres was measured, the concentrations of inflammatory factors, tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) in the cortex were measured, and the levels of neurotransmitters in the brain were determined. Preconditioning of CrCi-CDs significantly reduced ischemic lesion volume and blood–brain-barrier (BBB) permeability, improved neurologic deficits, decreased the level of TNF-α and IL-6 in MCAO rats, inhibited excitatory neurotransmitters aspartate (Asp) and glutamate (Glu), and increased the level of 5-hydroxytryptamine (5-HT). The RNA-Sequencing results reveal that further potential mechanisms behind the activities may be related to the anti-inflammation effects and inhibition of neuroexcitatory toxicity. Conclusion CrCi-CDs performs neuroprotective effect on cerebral ischemia and reperfusion injury, and the mechanisms may correlate with its anti-inflammatory action, which suggested that CrCi-CDs have potential value in clinical therapy on the acute apoplexy cases in combination with thrombolytic drugs. Graphic abstract